PERAN AL-QUR’AN DALAM MEMBAHAS KONSEP KESETARAAN GENDER DAN HAK ASASI MANUSIA: STUDI ATAS PRINSIP KEADILAN, MARTABAT, DAN HAK INDIVIDU - Dani Abdu Latief; Muhamad Adji Saputra; Sholahuddin Al Ayubi (Adisam Publisher, 2025)
This article explores the normative input of the Qur’an in the emerging values of gender equality and human rights in the light of three-proposed main principles: justice (ʿadl), dignity (karāmah), and individual rights (ḥuqūq al-fard). This research emerged following the desire to deconstruct religious knowledge that has been mostly encoded with patriarchal interpretation and local culture that restricts roles and freedoms women. This article applies a qualitative approach in the form of literature study and thematic interpretation analysis (mawḍū‘ī), and aspires to bring some focus to the contribution of our contemporary scholars in order to develop Islamic discourse that is gender-just and human rights-focused. The results of the research reveal that, far from merely tolerating the concepts of equality and toleration, the Qur'an constitutes a robust normative model for the realization of human rights in an emancipatory, inclusive and transcendent way. An exploratory article to draw attention to the necessity for a critical and contextual reading of to counter misinterpretations that minimize the rights of women and other suchlike categories.